Strengthening Financial Capabilities and Entrepreneurial Skills of Indonesian Migrant Workers in Penang, Malaysia - Puspitasari, Devy Mawarnie; Bachtillah, Andriansyah (Pascasarjana Universitas Mataram, 2025)
This community engagement program aims to enhance financial literacy and entrepreneurial readiness among Indonesian Migrant Workers (TKI) in Penang, Malaysia. Many TKI, particularly those employed in the informal sector, face significant challenges in managing personal finances and lack the necessary skills to initiate small businesses. In collaboration with the NGO Permai Malaysia, this program offers participatory training that covers basic financial management, daily expense tracking, savings and debt planning, as well as the development of simple micro-enterprises. The program is designed using a Participatory Action Research (PAR) approach and employs Gap Analysis to identify learning needs. The results indicate a significant improvement in participants’ knowledge and confidence in financial management, with many expressing enthusiasm and readiness to apply the skills acquired. The success of this initiative highlights the importance of practical and context-relevant education in empowering migrant workers towards economic independence. This activity supports the Sustainable Development Goals (SDGs), particularly in the areas of quality education, decent work, and reduced inequalities.